Meningkatkan Efektivitas Pemungutan dan Pelaporan Pajak Desa melalui Implementasi Sistem Administrasi Berbasis Teknologi Informasi - Adisiswanto, Alissa Ernawati; Nugraini , Dili Prelina (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
To analyze the effectiveness of village tax collection and reporting through the implementation of an information technology-based administration system. The method used is qualitative with a literature study approach within the last five years that is relevant to the digitization of village tax administration. The results of the study show that the implementation of digitization has a significant impact on improving process efficiency, data accuracy, transparency, and compliance in village tax reporting. Digitization not only speeds up the administrative process but also minimizes recording errors and strengthens the accountability of village governments. The main supporting factors for the successful implementation of this system are technical training for village officials and active community participation in understanding and using the digital system. However, the challenges faced are quite complex, particularly related to the low digital literacy of some communities and limited technological infrastructure in rural areas. The research recommendations emphasize the importance of accelerating the digitization of village tax administration, strengthening technological infrastructure, and continuously involving the community to create modern, transparent, and accountable village tax governance. These findings are expected to serve as a basis for public policy formulation and encourage innovation in village tax management in Indonesia, enabling villages to adapt to technological developments while improving the quality of public services